Rancang Bangun Sistem Pemeliharaan Jalan dan Jembatan Provinsi Jawa Barat - Nugraha, Fajar Rizki; Herwanto, Patah (STMIK Banjarbaru, 2024)
The SIPELAJAR application was developed to support the Technical Implementation Units (UPTD) I to VI at the West Java Province Department of Highways and Spatial Planning in conducting Sapu Lobang surveys and inputting Routine Work data. This study aims to design and develop a mobile-based application that enhances the efficiency of information management related to road and bridge maintenance. The system development method follows the System Development Life Cycle (SDLC) prototyping model, which includes stages such as requirements analysis, system design, application development, testing, implementation, and maintenance. The application features Geographic Information System (GIS) integration, enabling real-time visualization of pothole data. System testing was conducted using the Black Box Testing method to evaluate functionality, including data input validation, GIS visualization accuracy, and reporting and notification effectiveness. The findings indicate that SIPELAJAR enhances damage detection accuracy, speeds up the reporting process, and supports transparency in infrastructure management. The implementation of this application is expected to optimize the use of information technology in road and bridge maintenance, ultimately improving public services.Keywords: SIPELAJAR; Road and Bridge Infrastructure; Infrastructure Maintenance; GIS AbstrakAplikasi SIPELAJAR dikembangkan untuk mendukung Unit Pelaksana Teknis Dinas (UPTD) I hingga VI di Dinas Bina Marga dan Penataan Ruang Provinsi Jawa Barat dalam pelaksanaan survei Sapu Lobang serta penginputan data Pekerjaan Rutin. Penelitian ini bertujuan untuk merancang dan mengembangkan aplikasi berbasis mobile yang dapat meningkatkan efisiensi pengelolaan informasi pemeliharaan jalan dan jembatan. Metode pengembangan sistem menggunakan System Development Life Cycle (SDLC) model prototyping, yang meliputi tahapan analisis kebutuhan, perancangan sistem, pengembangan aplikasi, pengujian, serta implementasi dan pemeliharaan. Aplikasi ini dilengkapi fitur Geographic Information System (GIS) yang memungkinkan visualisasi data lubang secara real-time. Pengujian dilakukan menggunakan metode Black Box Testing untuk mengevaluasi fungsionalitas sistem, termasuk validasi input data, ketepatan visualisasi GIS, serta efektivitas pelaporan dan notifikasi. Hasil penelitian menunjukkan bahwa SIPELAJAR mampu meningkatkan akurasi deteksi kerusakan, mempercepat proses pelaporan, dan mendukung transparansi dalam pengelolaan infrastruktur. Implementasi aplikasi ini diharapkan dapat meningkatkan pemanfaatan teknologi informasi dalam pemeliharaan jalan dan jembatan guna memberikan pelayanan yang lebih baik kepada masyarakat.